Mineralogical Characteristics and Critical Stress Variation in Rock Samples from Bukit Kunyit, Bandar Lampung - Setiawan, Muhamad Ragil; Hilman, Zaki; Haqiqi, Rian Bayu; Farishi, Bilal Al (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Mineralogy is essential for understanding rock formation processes and their physical properties, including critical stress. Critical stress values can be estimated using unconfined compressive strength (UCS) measurements, which depend on the modulus values of the minerals present. This study explores the mineralogical characteristics of rock samples from Bukit Kunyit, Bandar Lampung City, and Lampung through X-ray diffraction (XRD) and petrographic analysis. Macroscopic observations revealed two visually distinct rock samples: one with a bright color (Sample 1) and another with a darker hue (Sample 2). Despite these color differences, XRD analysis showed that both samples have the same mineral composition, including Anorthoclase, Cristobalite, Tridymite, and Muscovite, indicating a felsic (silica-rich) nature. Differences were noted in the crystallographic forms of Muscovite and Quartz content, with Sample 2 having a higher Quartz concentration. These mineralogical variations correlate with the observed differences in critical stress, with Sample 1 exhibiting a lower critical stress (20.98 MPa) than Sample 2 (35.05 MPa).